Effects of intermittent treatment with parathyroid hormone (PTH) on osteoblastic differentiation and mineralization of mouse induced pluripotent stem cells in a 3D culture model. (25th June 2020) - Sato, Masahiro; Aoki, Hideto; Nakamura, Takashi; Onodera, Shoko; Yamaguchi, Akira; Saito, Atsushi; Azuma, Toshifumi
Abstract: Background/Objectives: PTH plays an important role in bone remodeling, and different actions have been reported depending on its administration method. iPSCs are promising as a cell source for regeneration of periodontal tissue due to their ability of proliferation and pluripotency. However, the effects of PTH on iPSCs remain mostly unknown. The purpose of this study was to investigate in vitro effects of parathyroid hormone (PTH) on osteoblastic differentiation of induced pluripotent stem cells (iPSCs) in a 3D culture model. Materials and Methods: Following embryoid body (EB) induction from mouse iPSCs (miPSCs), dissociated cells (miPS‐EB‐derived cells) were seeded onto atelocollagen sponge (ACS) in osteoblast differentiation medium (OBM). Cell‐ACS constructs were divided into three groups: continuous treatment with human recombinant PTH (1‐34) (PTH‐C), intermittent PTH treatment (PTH‐I) or OBM control. To confirm the expression of PTH receptor‐1(PTH1R), the expression of Pth1r and cAMP production over time were assessed. Real‐time PCR was used to assess the expression of genes encoding osterix ( Sp7 ), runt‐related transcription factor 2 ( Runx2 ), collagen type 1 ( Col1a1 ), and osteocalcin ( Bglap ) at different time points. Mineralization was assessed by von Kossa staining. Histochemical staining was used to analyze alkaline phosphatase (ALP) activity, and immunolocalization of SP7 and BGLAP was analyzed by confocal laser scanning microscopy (CLSM). Results: On days 7 and 14, expression of the Pth1r in miPS‐EB‐derived cells was increased in all groups. Production of cAMP, the second messenger of the PTH1R, tended to increase in the PTH‐I group compared with PTH‐C group on day 14. Expression of Col1a1 in the PTH‐I group on day 14 was significantly higher than other groups. There was a time‐dependent increase in the expression of Sp7 in all groups. On day 14, the expression level of Sp7 in the PTH‐I group was significantly higher than other groups. In von Kossa staining, the PTH‐I group showed higher level of staining compared with other groups on day 14, whereas the level was slightly attenuated in the PTH‐C group. In histochemical staining, ALP‐positive cells were significantly increased in the PTH‐I group compared with other groups on day 14. In CLSM analysis, the numbers of SP7‐ and BGLAP‐positive cells showed a gradual increase over time, and on day 14, a significantly greater SP7 expression was observed in the PTH‐I group than other groups. Conclusion: These results suggested that the intermittent PTH treatment promotes osteoblastic differentiation and mineralization of miPSCs in the ACS scaffold.